Analysis of The Ease of Use Paylater on Impulse Buying Through Shopping Lifestyle as an Intervening Variable - Mohammad Fikri Alghiffari; Kokom Komariah; Faizal Mulia Z (Dinasti Publisher, 2025)
ShopeeFood as a food delivery service that uses a digital platform that provides a practical Paylater feature with purchases without direct payment. This convenience increases Impulse Buying behavior which is influenced by the online Shopping Lifestyle. This study aims to determine the effect of Paylater and Shopping Lifestyle on Impulse Buying, and how the influence of Shopping Lifestyle in mediating the relationship between Paylater and Impulse Buying on Gen Z ShopeeFood consumers in Sukabumi City. This study uses quantitative methods with an associative approach. The sampling technique in this study used probability sampling method, namely purposive sampling with a total of 150 Gen Z ShopeeFood consumers in Sukabumi City who were respondents. The data analysis technique used in this research is Structural Equation Modeling using Partial Least Square. The results of this study indicate that there is a positive and significant effect of Paylater on Shopping Lifestyle, a positive and significant effect of Shopping Lifestyle on Impulse Buying and Paylater has a positive and significant effect on Impulse Buying on Gen Z ShopeFood consumers in Sukabumi City.